Altitudinal zoning of Pinus patula from cones and seeds in the sierra de Huayacocotla, Veracruz, Mexico - Aparicio-Rentería, Armando; Viveros-Viveros, Héctor; Hernández-Villa, Julia; Sáenz-Romero, Cuauhtémoc; Ruiz-Montiel, César; Pineda Posadas, Jorge Alberto (Instituto de Ecología, A.C., 2020)
Populations of forest species with a wide distribution tend to differ in morphological traits across altitudinal gradients. This allows the provisional zoning for conducting seed movement that ensures the adaptation and the best growth of the plants. The pattern of morphological variation associated with altitudinal gradients is not known for many Mexican pine species. Therefore, the altitudinal morphological variation was explored based on the length and width of cones and seeds of 70 Pinus patula plus trees selected in eight populations of Huayacocotla, Veracruz, to establish provisional zones for seeds movement. Analysis of variance and association with geographical variables were performed. Significant variation was recorded between and within populations for all the evaluated characteristics and positive correlation of the altitude with the characters of the cones and the width of the seeds. Based on the variation of cone length and width as well as seed width, we suggest a provisional delineation of two altitudinal seed zones (zone I: 1850 m - 2350 m asl; zone II: 2350 m - 2850 m asl), for the movement of seed and reforestation. It is suggested that the seed collected in each zone is used provisionally in a range of ± 250 altitudinal m from the place of origin, without considering the effects climate change. Considering climatic change, it is suggested an altitudinal upward shift of seed sources of 250 m of altitude to realign to the climate projected for 2030, or 500 m for the one to 2060.